The Influence Of Product Brand, Product Quality And Sales Promotion On Purchasing Decisions Fashion Products At The Ratu Collection Shop - Fitri Handayani Harefa; Krisnawati Setyaningrum Nugraheni (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research was conducted at Toko Ratu Collection Stores which aims to analyze and explain the influence of product brands, product quality and sales promotions on purchasing decisions for fashion products which are experiencing unfavorable conditions including product sales promotions in social networks which cannot be ascertained because currently there are still many consumers who cannot use social media. Research data obtained through questionnaires and interviews. The sample used in the study was 100 respondents. The research results are expected to provide useful information for managers and consumers. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses multiple regression analysis to determine the effect of the independent variable on the dependent variable, test the model, test the hypothesis, and but before carrying out the test, the validity and reliability tests are carried out first. The results of the regression analysis show that there is an increase in product branding, product quality and sales promotion on the purchasing decision of fashion products. So the results of the multiple regression analysis test show a significant F value, with a correlation value of determination R2 square of 0.629. This shows that product brand, product quality and sales promotion significantly influence the purchasing decision of fashion products together with a close relationship of 62.9%. This shows that to increase purchasing decisions for fashion products, it is necessary to increase product brands, product quality and sales promotions that are popular today..